THE THE RELATIONSHIP BETWEEN VULVAR HYGIENE BEHAVIOR DURING MENSTRUATION AND THE INCIDENCE OF VAGINAL DISCHARGE (FLOUR ALBUS) IN ADOLESCENT WOMEN - Ratnasari, Rheka; Setiyawan; Shovie Rizqiea, Noerma (Disease Prevention and Public Health Journal, 2025)
Background : Vaginal discharge or flour albus refers to the non-bloody discharge other than blood from the vagina under normal conditions. Physiological vaginal discharge is considered normal for women, whereas abnormal or pathological discharge refers to any discharge that deviates from the usual characteristics or quantity typically observed under healthy conditions.  Vulvar hygiene is a particular care for women to maintain the external reproductive area. The study aimed to determine the relationship between vulvar hygiene behavior during menstruation and the incidence of vaginal discharge (flour albus) in adolescent women at Senior High School 8 Surakarta. Method : This research design employed quantitative using an analytic correlation study with the cross-sectional method. The sample selected 68 respondents of Senior High School 8 Surakarta students using the Slovin formula with proportional stratified random sampling. The analysis utilized the gamma test to examine the relationship between variables. Results: The results of the gamma test demonstrated a (P-Value 0.007 <0.05), which indicated a relationship between vulvar hygiene behavior and the incidence of vaginal discharge (flour albus). Conclusion : It concluded a significant relationship between vulvar hygiene behavior and the incidence of vaginal discharge (flour albus) in adolescent women at Senior High School 8 Surakarta. This study suggests that every woman could maintain the external reproductive organs by accomplishing vulvar hygiene practices to reduce vaginal discharge (flour albus).